2017
DOI: 10.1016/j.jor.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of hip or knee arthroplasty in patients with cirrhotic liver disease

Abstract: Objective: Present helpful measures to prevent expected complications that occur in patients with liver cirrhosis undergoing arthroplasty. Methods: 218 patients who underwent hip or knee arthroplasty were included in this study. Prognoses of patients with underlying disease of liver cirrhosis and those without are compared with measures. Results: Patients with liver cirrhosis show an increase in amount of bleeding, hospital stay and infection rate compared to those who do not. Conclusion: The risk of arthropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
12
1
1
Order By: Relevance
“…A total of 26 relevant article titles were identified. After application of eligibility criteria described, eight studies [11–18] qualified for inclusion. Two further studies [19, 20] reported on outcomes of THA in patients post liver transplantation for CLD, and this was deemed an interesting group for comment separately.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 26 relevant article titles were identified. After application of eligibility criteria described, eight studies [11–18] qualified for inclusion. Two further studies [19, 20] reported on outcomes of THA in patients post liver transplantation for CLD, and this was deemed an interesting group for comment separately.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported on implant failure and revision rates [11–13, 16–18]. There was an increased rate of revision surgery at 4% (46/1083 THAs) compared with 0.2% in controls ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations